High resolution front-side visualization of charge stored in EEPROM with scanning nonlinear dielectric microscopy (SNDM) - Zeng, Xiaomei (2022)
By exposing floating gates of EEPROM memory cells with frontside sample preparation, scanning nonlinear dielectric microscopy (SNDM) succeeded in reading back the data stored in the memory cells with a 250 nm node size. At an optimized voltage bias of AC = 3 V and DC = 1 V, a clear signal contrast between programmed and erased cells is obtained. The high resolution SNDM signal reveals the details of bowling-pin shape structure of memory cells, providing high confidence in data assignment during forensic applications. Such high resolution also makes SNDM a promising technique for newer generation devices with smaller node size.